Nurses' Knowledge of Hospital Safety in A Tertiary Healthcare Setting - Athirarani M․R․; Ajayan Kamalasanan; Vinoth Raman; Jibina John; Lekshmi R․; Liji C․; Preetha S․; Rejani A․V․; Reshma S․R․; Roshni K․P․ (Next Research, 2025)

Comparative investigation of structural properties and biological applications of chemical and biogenic synthesis of zirconium dioxide (ZrO2) nanoparticles using Passiflora edulis - Preetha S; Anilkumar P; Nisha Jenifar A (Journal of Photochemistry and Photobiology B: Biology, 2025)

Effect of Bacillus thuringiensis B. δ-endotoxin (Cry1Ac) on the biological and life table characteristics of tobacco cutworm, Spodoptera litura F - M. Kannan; A. Nasreen; K. Elango; S. Preetha; K. Govindaraju (International Journal of Tropical Insect Science, 2024)

Cryopreservation of shoot meristems of Baliospermum montanum (Willd.) Muell. Arg. for long-term conservation and sustainable utilization - K. P. Parvathi; T. S. Preetha; A. S. Hemanthakumar (Vegetos, 2023)

Comparative analysis of carbon emission from products of virgin plastics and recycled plastics and their environmental benefits - A. Ganesan; H. Preetha; S. Subathara; S. Bhowmik (International Journal of Environmental Science and Technology, 2023)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

Assessing hydrogeochemistry, water quality index (WQI), and seasonal pattern of plankton community in different small and medium reservoirs of Karnataka, India - Preetha Panikkar; Ajoy Saha; A. K. Prusty; Uttam Kumar Sarkar; Basanta Kumar Das (Arabian Journal of Geosciences, 2022)

An insight into in vitro strategies for bioproduction of isoflavones - Nandakumar Vidya; Krishnagowdu Saravanan; Jayachandran Halka; Kumaresan Kowsalya; Jaganathan Sakthi Yazhini Preetha; Packiaraj Gurusaravanan; Ramalingam Radhakrishnan; A. Usha Raja Nanthini; Muthukrishnan Arun (Plant Biotechnology Reports, 2021)

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Report from a symposium on catalyzing primary and secondary prevention of cancer in India - Suneeta Krishnan; Preet K. Dhillon; Afsan Bhadelia; Anna Schurmann; Partha Basu; Neerja Bhatla; Praveen Birur; Rajeev Colaco; Subhojit Dey; Surbhi Grover; Harmala Gupta; Rakesh Gupta; et al. (Cancer Causes & Control, 2015)

Modelling the food web for assessment of the impact of stock supplementation in a reservoir ecosystem in India - M. F. Khan; P. Preetha; A. P. Sharma (Fisheries Management and Ecology, 2015)
Comparative estimates of trophic status and energy flow were carried out in a tropical reservoir ecosystem in India to assess the impact of fish stocking. Mass‐balanced models of the reservoir ecosystem were constructed for two periods – 1982–1983 and 2002–2003 – using ecopath software to determine the impacts on different groups before and after stocking. Mixed trophic impact ( MTI ) analyses indicated that phytoplankton and detritus have a positive impact on most groups. There was a decrease in nutrient flow through the system from pre‐stocking to post‐stocking (22.28%). The baseline was higher by 0.29% in the post‐stock phase indicating maturity. The ecosystem indices tested indicate that the reservoir was in a more resilient state post‐stocking than during the pre‐stocking phase. The ‘health’ of the ecosystem showed an improvement, which indicates a positive impact of stocking.

Characterizing trophic interactions of a catfish dominated tropical reservoir ecosystem to assess the effects of management practices - Preetha Panikkar; M. Feroz Khan; V. R. Desai; N. P. Shrivastava; A. P. Sharma (Environmental Biology of Fishes, 2015)

Parmotrema tinctorum exhibits antioxidant, antiglycation and inhibitory activities against aldose reductase and carbohydrate digestive enzymes: an in vitro study - P. Salin Raj; A. Prathapan; Jomon Sebastian; Antu K. Antony; Mariam Philip Riya; M.R. Preetha Rani; H. Biju; S. Priya; K.G. Raghu (Natural Product Research, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Why conservationists should be concerned about natural resource legislation affecting indigenous peoples’ rights: lessons from Peninsular Malaysia - Sheema A. Aziz; Gopalasamy R. Clements; D. M. Rayan; Preetha Sankar (Biodiversity and Conservation, 2013)

Insight in glioma susceptibility through an analysis of 6p22.3, 12p13.33-12.1, 17q22-23.2 and 18q23 SNP genotypes in familial and non-familial glioma - Yanhong Liu; Beatrice S. Melin; Preetha Rajaraman; Zhaoming Wang; Martha Linet; Sanjay Shete; Christopher I. Amos; Ching C. Lau; Michael E. Scheurer; Spiridon Tsavachidis; Georgina N. Armstrong; Richard S. Houlston; et al. (Human Genetics, 2012)

Impact of Tropical Ecosystem on the Migrational Behavior of K-40, Cs-137, Th-232 U-238 in Perennial Plants - Ajay Kumar; R. K. Singhal; J. Preetha; K. Rupali; U. Narayanan; Sughandhi Suresh; Manish K. Mishra; A. K. Ranade (Water, Air, & Soil Pollution, 2008)

Effect of Fluidizing Agents on Paclitaxel Penetration in Cervical Cancerous Monolayer Membranes - A. Preetha; N. Huilgol; R. Banerjee (The Journal of Membrane Biology, 2007)

Determination of Ultra Trace Level of Uranium in Ground Water of Different Geo-Chemical Environment by Adsorptive Stripping Voltammetry - R. K. Singhal; V. M. Joshi; J. Preetha; Rupali Karpe; Ajay Kumar; A. G. Hegde (Water, Air, & Soil Pollution, 2007)